Effect of Dimethyl Sulfoxide and Diethyl Sulfoxide on Thermal Denaturation of Human Serum Albumin - Grigoryan, K. R.; Markarian, S. A.; Aznauryan, M. G. (Problems of Cryobiology and Cryomedicine, 2009)
The effect of dimethyl sulfoxide (DMSO) and diethyl sulfoxide (DESO) on thermal (heat and cold) denaturation of human serum albumin within temperature range from â€“20 to90Â°Cwas investigated by electron and fluorescent spectroscopy. It has been established that at heat induced denaturation in the presence of DESO an acid-neutral transition was observed at 47.61Â°C. It was shown that at cold induced denaturation the direct hydrophobic interactions of sulphoxide molecules with protein surface result in the formation of stable â€œiceâ€ layer, providing the protein protection from irreversible structure changes.